Recent developments in the detection and management of acute kidney injury. Issue 1 (5th August 2016) - McCaffrey, James; Dhakal, Ajaya Kumar; Milford, David V; Webb, Nicholas J A; Lennon, Rachel
Abstract : Acute kidney injury (AKI) is a common condition in children admitted to hospital and existing serum and urine biomarkers are insensitive. There have been significant developments in stratifying the risk of AKI in children and also in the identification of new AKI biomarkers. Risk stratification coupled with a panel of AKI biomarkers will improve future detection of AKI, however, paediatric validation studies in mixed patient cohorts are required. The principles of effective management rely on treating the underlying cause and preventing secondary AKI by the appropriate use of fluids and medication. Further therapeutic innovation will depend on improving our understanding of the basic mechanisms underlying AKI in children.